EFEKTIVITAS MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS V SD MUHAMMADIYAH KARANGPLOSO - Siwi Purwanti; Nuraini Dwi Saputri (Universitas Sarjanawiyata Tamansiswa, 2020)
The background of this study is the low value of students in science subjects. The purpose of this research is to determine the effectiveness of the application of the Make A Match cooperative learning model to the learning outcomes of the fifth grade science students at Muhammadiyah Elemantary School of Karangploso. This research is quasi-experimental, with Pretest Posttest Control Group Design. The population isÂ all of fifth grade students which isÂ consisted of two classes with a total of students are 66 students. The data collection techniques for students' cognitive learning outcomes used test method. Initial data analysis used the normality test and homogeneity test. While the final data analysis used paired sample t-test.The results of this research are, the results obtained an average pretest value of 56,67 and an average posttest value of 74,04 with Std. Pretest deviation = 7,217 and Std. Posttest deviation = 8,770. The results of t-test calculations helped by using SPSS 23 with Î± = 0,05 and get the results that the value of sig. (2-tailed) 0,00 <0,05 and tcount = -10,514 with df which is 32 which means that ttable = 2,036. Tcount is negative because between the pretest and posttest values have quite a large differences, and in the cases like this, the negative value will be change to a positive value. This showed that tcount> ttable, then H1 is accepted or learning with Make A Match method is effective against student learning outcomes in science subjects in V class, with an average posttest score for the experimental class of 74,04.